2020
DOI: 10.1038/s41433-020-1093-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of general anaesthesia on intraocular pressure in paediatric patients: a systematic review

Abstract: Objectives Assessment of the impact of general anaesthetic agents on intraocular pressure (IOP) in children via systematic review. Methods Pubmed, Embase, and CENTRAL databases were systematically searched to identify randomised controlled trials, prospective, and interventional studies. The search included all studies through October 5, 2018 with no date or language restrictions. A linear mixed-effects regression analysis was performed to study the change in IOP after general anaesthesia (GA). ResultsThe stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…In our study, as compatible with other studies, IOP values were found to be low after induction and high after intubation compared to pre-induction values in less than three-year assistant groups [ 1 , 2 , 10 , 11 ]. This increase in IOP is within normal limits.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, as compatible with other studies, IOP values were found to be low after induction and high after intubation compared to pre-induction values in less than three-year assistant groups [ 1 , 2 , 10 , 11 ]. This increase in IOP is within normal limits.…”
Section: Discussionsupporting
confidence: 93%
“…Tracheal intubation can cause an increase in intracranial pressure, which can lead to an increase in IOP. However, it is important to note that the effect of IOP can vary greatly between patients and depends on several factors, such as the individual's anatomy and the method of intubation [ 1 , 2 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple factors can affect IOP pressure readings before surgery such as breath-holding, Valsalva maneuvers, corneal irregularities, and inhalational anesthetic agents. 8 , 9 As inhalational anesthetics can significantly impact IOP, 9 the IOP reading OD prior to surgery did not guide treatment. Rather, persistently elevated pressures in clinic with the presence of glaucomatous damage indicated necessity for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Because the dogs were also anesthetized before the IVT injections, the residual effects of the anesthetics could also have lowered the IOP as has been reported in many mammalian species. [33][34][35] Subsequently, a small insignificant increase in IOP was observed in the injected eye from day 29 to week 8. However, this increase was not significantly different from the baseline or from the AAV2-injected eyes.…”
Section: Iop Measurementsmentioning
confidence: 96%